Criteria, Procedures, and Future Prospects of Involuntary Treatment in Psychiatry Around the World: A Narrative Review - Saya, Anna; Brugnoli, Chiara; Piazzi, Gioia; Liberato, Daniela; Di Ciaccia, Gregorio; Niolu, Cinzia; Siracusano, Alberto (Frontiers in Psychiatry, 2019)
The use of involuntary treatments in psychiatry comes with some benefits and many disadvantages for the patient’s experience and the therapeutic outcome. This review proposes to compare the procedures and criteria for involuntary psychiatric treatment and to outline the current situation concerning the relevant legislation and practices around the world. Various historical and present-day criteria and procedures are described and compared, showing a certain degree of heterogeneity to this day. Studies relating to patient experiences of coercive measures and their effects on the therapeutic relationship and continued adherence are examined. The breach of the principle of self-determination appears as a central element of the critique; underlined both in clinical reality and in jurisprudence. Moreover, assessment of the patient's decision-making capacity regarding their own care, the use of advance treatment directives, and the reduction of the mental patient's stigma in favour of greater social and therapeutic support appear important. We highlight the similarities and differences between legislation and practice in various parts of Europe, North America, Asia, and some areas of Latin America, Africa and the South Pacific. Other aspects that we explored include the patient’s experience of coercion; the repercussions on the therapeutic relationship and adherence to treatment following coercion; the role it plays in the prevention of suicide; ethical problems; and possible alternatives to reduce the use of coercive measures.